Musical Life in Montreal's Judeo-Spanish Community - Cohen, Judith R. (Garland Encyclopedia of World Music, tome III : United States and Canada, 2001)

Des mondes religieux parallèles, un espace commun? Amérindiens et musique vocale européenne sous le Régime français - Dubois, Paul-André (Études d'histoire religieuse, 2001)
This article is devoted to the question of French religious music used by Christian Indians of New France during the 17th and 18th centuries. More particularly, it examines the surprising success of this religious and artistic practice in the post-contact North American world. It appears that cultural more than geopolitical or socioeconomic factors can explain the rapid adoption of European religious songs by Indians. In my opinion, only a better understanding of the role traditionally held by singing in the Indian culture could help us identify the cultural basis on which such a success is based. From there, it becomes possible to sustain a larger reflection about Catholicism's influence among Indians during the historical period.

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)

La semaine annuelle de musique de Montréal sous les auspices du Delphic Study Club, 1923–1937 - Lefebvre, Marie-Thérèse (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
This study begins with an examination of the background against which was founded the annual Music-Week in Montreal (1923–1937), then presents an analysis of its system of operation, inspired by the American model created in 1920 by Charles Milton Tremaine. Information on the staff of the association, its sponsors, financial grants, concert venues, performers, repertory, and lecturers is discussed; the main points of the press reviews of the events are extracted. The anglophone-francophone cultural dualism with regard to the conception of music and of its role in education emerges clearly in the conclusion, which also highlights the active role of women in the running of organizations destined to spread music in Quebec.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Chansons de cours-nu-pieds - Miville-Deschênes, Monique (Éditions Triptyque, 2001)

Three moments of love in Leonard Cohen and Bruce Cockburn - Nonnekes, Paul (Black Rose Press, 2001)
"Three Moments of Love is a series of reflections on the work of Leonard Cohen and Bruce Cockburn. These two artists, so different in style and temperament, are brought together in one work in order to compare and examine the way in which they approach the question of love and desire: in their art and in their life."

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

L’homosexualité dans la chanson : du bout des lèvres - Perron, Gilles (Québec français, 2001)
Publisher: Les Publications Québec français

Archéologie sonore. Chants amérindiens - Tremblay-Matte, Cécile; Rivard, Sylvain (Éditions Trois, 2001)
Traduit l'importance historique et culturelle des chants traditionnels des dix nations amérindiennes du Québec. Certains d'entre eux sont parvenus à passer outre l'évangélisation et l'influence de la culture européenne. Textes en langue autochtone et transcription des mélodies.

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian; Québécois; anglophone; francophone; music; newspapers; politics